1996
DOI: 10.1074/jbc.271.44.27304
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Neurocan Structures Interacting with the Neural Cell Adhesion Molecule N-CAM

Abstract: Neurocan is a brain-specific chondroitin sulfate proteoglycan, which has been shown to bind to the neural cell adhesion molecule N-CAM and to inhibit its homophilic interaction. To study in more detail the structures of neurocan responsible for this interaction, various recombinant neurocan fragments were generated. The ability of these fragments to interact with N-CAM was investigated in several different in vitro assay systems, enzyme-linked immunosorbent assaytype binding assays, Covasphere-aggregation assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 20 publications
1
52
0
Order By: Relevance
“…Neurocan message and protein were found in many parts of the brain, but not ubiquitously (6,22). Neurocan can bind to N-CAM, Ng-CAM, and axonin and interfere with the cell adhesive function of Ng-CAM (10,27,42). In vitro experiments showed a direct repulsive effect of neurocan on neurons and an inhibition of neurite outgrowth (8), suggesting that developmentally regulated neurocan expression in certain regions of the brain will have a significant impact on axon guidance and fasciculation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurocan message and protein were found in many parts of the brain, but not ubiquitously (6,22). Neurocan can bind to N-CAM, Ng-CAM, and axonin and interfere with the cell adhesive function of Ng-CAM (10,27,42). In vitro experiments showed a direct repulsive effect of neurocan on neurons and an inhibition of neurite outgrowth (8), suggesting that developmentally regulated neurocan expression in certain regions of the brain will have a significant impact on axon guidance and fasciculation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it binds with high affinity to the neural cell adhesion molecules Ng-CAM/L1 (10), axonin (27), and N-CAM (42), which show an overlapping expression with neurocan. The N-terminal domain of neurocan mediates the binding to hyaluronan (43).…”
mentioning
confidence: 99%
“…Experiments were performed and affinities were calculated in essentially the same way as described earlier (36), in part, with the identical covalently immobilized ligands.…”
Section: Quantitation Of Affinities Of Neurocan Interactions With Tenmentioning
confidence: 99%
“…Retzler et al have shown that N-CAM binds to all major components of neurocan using various recombinant neurocan fragments [41]. Their results suggest that both neurocan-C and the N-terminal fragments are able to bind to N-CAM.…”
Section: Biological Functions Of Neurocan and Its Fragmentsmentioning
confidence: 94%